Application of Microwave Techniques in Textile Chemistry - Haghi, A.K. (Asian Journal of Chemistry, 2016)
Microwave heating techniques have been widely used in textile chemistry. This paper presents a state-of-the-art review of microwave technologies and industrial applications. The characteristics of microwave interactions with textile materials are outlined together with microwave fundamentals in the heat-setting process. Furthermore, the limitations in current understanding are included as a guide for potential users and for future research and development activities.